Serangan Hama Bunga Kelapa Tirathaba rufivena Walker (Lepidoptera : Pyralidae) pada Tanaman Kelapa Genjah Salak di Kebun Percobaan Kima Atas - MELDY L.A. HOSANG (Pusat Penelitian dan Pengembangan Perkebunan, 2010)
Incidence of the greater coconut spike moth Tirathaba rufivena Walker (Lepidoptera, Pyralidae) on Salak Dwarf Coconut at Kima Atas Experimental GardenThe objectives of this research is to study the incidence of (Walker) pest inSalak Dwarf coconut (GSK) at experimental garden Kima Atas, North Sulawesi. The study was conducted from January to February 2007 by survey on Salak Dwarf plantation. Observation was done by counting the number of healthy and infected female flowers, larval population, symptoms of attacks, and the natural enemies. The results showed that of 647 palms observed, 118 palms (18.27%) are already flowering, and 529 (81.73%) palms have not yet bearing fruits. Of the total palms that are flowering or fruiting, 34.75% palms are not attacked and 65.25% palms were attacked by, which consisted of a light attack 20.34%, medium attack 22.88%, and heavy attack 22.03%.